Validitas Bahan Ajar Pengayaan Mata Kuliah Ekologi Lahan Basah Pokok Bahasan Lahan Basah Kalimantan Selatan Berbasis Hasil Penelitian Ikan di Sekitar Pulau Sirang Waduk Riam Kanan Kabupaten Banjar - Hardiansyah Hardiansyah; Noorhidayati Noorhidayati; Mahrudin Mahrudin (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2019)
The wetland environment can be used as a source of learning and teaching material, so that learning is carried out based on contextual learning. This study aims to describe the validity of ecology enrichment teaching materials on wetlands subject of wetlands in South Kalimantan based on the results of fish research around the Sirang Island, Riam Kanan Reservoir, Banjar Regency. This research method is research and development with 5 steps, identification of potential and problems, data collection, product design, design validation, and design revision. The results showed that teaching materials in the form of handouts that were developed as enrichment material for land ecology courses had very valid or were suitable for use. Readability test by 7 students who have passed the wetland ecology course gets very good criteria.